(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
In this paper we have tested various frequency scaling algorithm available in Linux and measured the effects of the different algorithms during operation in an actual system. We have tested all the default scaling algorithms included in Linux in a controlled testing environment and measured the actual effects of the scaling algorithms to the CPU power consumption during operation. In order to retain high accuracy and avoid unnecessary components from affecting the results, we have conducted the measurement directly on the CPU power supply line and logged the power usage in real time.